Studi Pengembangan Agroindustri di Kabupaten Jeneponto : Studi Kasus : Kawasan Perkotaan Mallasoro Dan Sekitarnya - Himanov , Muh Fiqhy; Aksa, Kamran; Yahya, Ilham (Fakultas Teknik Universitas Bosowa, 2023)
The agricultural sector is still the cornerstone of Jeneponto Regency. The urban area of Mallasoro and its surroundings is a coastal area with the potential for seaweed cultivation, agriculture, plantations, and animal husbandry. There are obstacles to the development of agro-industry in the research area, namely the lack of raw materials, low human resources, lack of use of agricultural technology, and lack of business partners. The analytical method used is the analysis of Location Quotient and Dynamic Location Quotient, which are combined to find out the leading commodities in the research area and its surroundings, and then an analysis of factors that are significant to the underdevelopment of agro-industry in the research area is carried out using chi-square analysis. and continued with a descriptive analysis in determining alternative strategies for minimizing the impact of significant factors on the underdevelopment of agro-industry in the urban area of Mallasoro and its surroundings. The results of the analysis provided directions and alternative strategies, namely: (1) carrying out various human resource capacity building programs so that they could be further improved by involving various parties, both private and public, including research institutions and universities. 2) Increasing the capacity of human resources can also maximize the application of agricultural technology for farmers so that agricultural products are abundant and able to produce quality raw materials independently, and the products produced are also of very good quality. This is also supported by the need to utilize superior agricultural commodities in Bangkala District, which are able to increase the availability of raw materials. As well as utilizing potential commodities such as corn and field rice as animal feed which are superior commodities.